2016
DOI: 10.1007/s10409-016-0588-9
|View full text |Cite
|
Sign up to set email alerts
|

Entropic force between biomembranes

Abstract: Undulation force, an entropic force, stems from thermally excited fluctuations, and plays a key role in the essential interactions between neighboring surfaces of objects. Although the characteristics of the undulation force have been widely studied theoretically and experimentally, the distance dependence of the force, which constitutes its most fundamental characteristic, remains poorly understood. In this paper, first, we obtain a novel expression for the undulation force by employing elasticity and statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…Given the resolved complex structure, the receptor-ligand binding affinity can be calculated from molecular dynamics simulations. Together with theoretical analyses and numerical simulations, experiments have revealed that (in sharp contrast to the typical experimental scenario of molecules binding in solution) the two-dimensional receptor-ligand binding affinity depends not only on the direct receptor-ligand interactions, but also on a number of other factors, e.g., the stiffness and thermal roughness of the adhering membranes ( Hu et al, 2013 ; Weikl et al, 2016 ; Li et al, 2017 ; Li and Song, 2018 ; Li et al, 2022 ), membrane curvature ( Li et al, 2019 ; He et al, 2021 ; An et al, 2022 ), physical parameters of the glycocalyx ( Paszek et al, 2014 ; Xiao et al, 2016 ; Xu et al, 2016 ; Kuo et al, 2018 ), and the length and flexibility of the receptor and ligand proteins ( Hu et al, 2015 ; Xu et al, 2015 ; Weikl et al, 2016 ; Li et al, 2021b ). In addition to the affinity K , also the cooperativity of binding should be taken into account to characterize the receptor-ligand binding during cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Given the resolved complex structure, the receptor-ligand binding affinity can be calculated from molecular dynamics simulations. Together with theoretical analyses and numerical simulations, experiments have revealed that (in sharp contrast to the typical experimental scenario of molecules binding in solution) the two-dimensional receptor-ligand binding affinity depends not only on the direct receptor-ligand interactions, but also on a number of other factors, e.g., the stiffness and thermal roughness of the adhering membranes ( Hu et al, 2013 ; Weikl et al, 2016 ; Li et al, 2017 ; Li and Song, 2018 ; Li et al, 2022 ), membrane curvature ( Li et al, 2019 ; He et al, 2021 ; An et al, 2022 ), physical parameters of the glycocalyx ( Paszek et al, 2014 ; Xiao et al, 2016 ; Xu et al, 2016 ; Kuo et al, 2018 ), and the length and flexibility of the receptor and ligand proteins ( Hu et al, 2015 ; Xu et al, 2015 ; Weikl et al, 2016 ; Li et al, 2021b ). In addition to the affinity K , also the cooperativity of binding should be taken into account to characterize the receptor-ligand binding during cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…32 Many life activities in nature are closely related to this, such as virus infection, cell migration, vesicle transportation, and fertilization. 33 Due to the different chemical properties and physical states of different proteins and lipids on the membrane, based on hydrophobic interactions, electrostatic interactions, van der Waals forces, hydrogen bonds and hydration forces, the membrane surface will form a variety of synergistic lipid raftprotein structure domains (surface pattern). These surface patterns are critically important in mediating life activities.…”
Section: Mechanism Of Biorecognition In Naturementioning
confidence: 99%
“…32 Many life activities in nature are closely related to this, such as virus infection, cell migration, vesicle transportation, and fertilization. 33…”
Section: Biorecognition Of Natural Molecules and Artificial Nanoparti...mentioning
confidence: 99%
“…A membrane-anchored receptor can bind to a ligand anchored in apposing membrane only if the local membrane separation at the protein site is within binding range. Therefore, the binding of receptor and ligand molecules depends strongly on the local separation of the two membranes, which varies in time and space due to the thermal shape fluctuations of flexible membranes ( Li and Song, 2016 ; Li and Song, 2018 ). As mentioned above, the intercellular communication process involves multiple length scales ranging from angstroms to micrometers.…”
Section: Protein-membrane Interactionmentioning
confidence: 99%